2016
DOI: 10.1021/acschembio.5b00948
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Integrase Strand Transfer Inhibitors with Reduced Susceptibility to Drug Resistant Mutant Integrases

Abstract: HIV integrase (IN) strand transfer inhibitors (INSTIs) are among the newest anti-AIDS drugs; however, mutant forms of IN can confer resistance. We developed noncytotoxic naphthyridine-containing INSTIs that retain low nanomolar IC50 values against HIV-1 variants harboring all of the major INSTI-resistant mutations. We found by analyzing crystal structures of inhibitors bound to the IN from the prototype foamy virus (PFV) that the most successful inhibitors show striking mimicry of the bound viral DNA prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
117
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(118 citation statements)
references
References 45 publications
1
117
0
Order By: Relevance
“…156 Furthermore, design of small molecules that more completely fill the substrate envelope within the intasome active site could lead to improved inhibitory properties. 358 …”
Section: Hiv-1 In As a Target For Drug Developmentmentioning
confidence: 99%
“…156 Furthermore, design of small molecules that more completely fill the substrate envelope within the intasome active site could lead to improved inhibitory properties. 358 …”
Section: Hiv-1 In As a Target For Drug Developmentmentioning
confidence: 99%
“…Overlaying the structures of INSTI-bound PFV intasomes to those of the SSC and TCC yielded important insight into the mechanism of drug action (16,112,113). The RAL metalchelating oxygen atom distal from the halobenzyl group coincided with the nucleophilic water molecule for IN 3Ј processing activity (red sphere in Fig.…”
Section: Instismentioning
confidence: 99%
“…Antiviral activities of DTG and our compounds against a panel of INSTIresistant single mutants. We previously measured the antiviral potencies of DTG and 4c, 4d, 4f, 6b, and 6p in single-round replication assays using WT HIV-1, well-established first-generation INSTI-resistant mutants, and selected putative DTG-resistant mutants (18,19). However, we had not previously determined the 50% effective concentrations (EC 50 s) for DTG and our compounds against many of the emerging INSTI-resistant mutants that have recently been identified in cell culture selection studies and clinical trials (10,30,31).…”
Section: Resultsmentioning
confidence: 99%
“…4c and 4d include alcohol-derived attachments, 4f is a disulfonophenyl derivative (19), and 6b and 6p contain ester-derived substituents (18). All of the compounds potently inhibit the replication of WT HIV-1, and we showed that the best of these compounds retain their potency against a number of the well-known INSTI-resistant mutants (18,19). That allowed us to choose the most promising of our new compounds for detailed analysis.…”
mentioning
confidence: 83%
See 1 more Smart Citation